2021
DOI: 10.2174/1386207324666210121111446
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals for Sleep Disorders

Abstract: : Sleep is considered as one of the most important aspect for maintaining a healthy life. For a person to function normally at least 6-8 hours of sleep daily is necessary. Sleep not only affects our mood, but also regulates the efficiency of work done. Many complications arise due to inadequacy of sleep. The unhealthy food and lifestyle choices have made us more prone to sleep disorders. The medications which are used for the treatment of sleep disorders are mainly habit forming and have tendencies of withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Therefore, there has been an increased interest in finding a new approach to sleep problems with fewer adverse effects. Based on this reason, there is increasing interest in nutraceuticals, which are safe even if taken for a long time, for the treatment of sleep disorders [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there has been an increased interest in finding a new approach to sleep problems with fewer adverse effects. Based on this reason, there is increasing interest in nutraceuticals, which are safe even if taken for a long time, for the treatment of sleep disorders [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmacological therapy for insomnia consists of cognitive behavioral therapy for insomnia (CBT-i), which is a type of therapy used for behavior and lifestyle changes, and complementary medicines including natural sleep aids and herbal remedies are used. Recently, interest in alternative medicines such as medicinal plants and dietary supplements has been growing, as although medication treatment has a fast and good effect on insomnia, there is a high potential for abuse and dependence [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of sleep also interferes with the weight loss achieved by caloric restriction, indicating the key role of sleep in terms of the efficacy of weight-loss strategies [ 269 ]. TRF and multiple natural bioactive compounds have been associated with an improvement in sleep [ 76 , 271 , 272 ].…”
Section: Mechanisms Of Chrononutrition In Energy Homeostasis and Obesitymentioning
confidence: 99%
“…Some studies have shown that the intake of certain nutrients and dietary supplements can improve sleep, in terms of both the length and quality ( 2 ). Compared to drugs, foods are more suitable for treating sleep diseases because they are non-toxic, have no withdrawal symptoms, and have higher efficacy ( 3 ). Among natural drugs, valerian, Hypericum perforatum , passionflower, and hops are all considered sleeping herbs for patients with insomnia ( 4 ).…”
Section: Introductionmentioning
confidence: 99%